Biological functions of PCAT-1/ SOX4 in cell proliferation and invasion of breast cancer: lncRNA PCAT-1 in breast cancer - Huang, Tao; Zhang, Jizong (Cellular and Molecular Biology, 2024)
Breast cancer (BC) is one of the most common fatal cancers. Recent studies have identified the vital role of long noncoding RNA (lncRNAs) in the development and progression of BC. In this research, lncRNA PCAT-1 was studied to identify how it functioned in the metastasis of BC. PCAT-1 expression of tissues was detected by real-time quantitative polymerase chain reaction (RT-qPCR) in 50 BC patients. Cell proliferation, wound healing assay and transwell assay were used to observe the biological behavior changes of BC cells through knockdown or overexpression of PCAT-1. In addition, RT-qPCR and Western blot assay were performed to discover the potential target protein of PCAT-1 in BC. PCAT-1 expression level in BC samples was higher than that of adjacent ones. Besides, cell proliferation, migrated ability and cell invaded ability of BC cells were inhibited after PCAT-1 was silenced. Cell proliferation, migration and invasion of BC cells were promoted after PCAT-1 was overexpressed. In addition, SOX4 was downregulated after silence of PCAT-1 in BC cells, while SOX4 was upregulated after overexpression of PCAT-1 in BC cells. Furthermore, SOX4 was upregulated in BC tissues and was positively associated with PCAT-1. Our study uncovers a new oncogene in BC and suggests that PCAT-1 could enhance BC cell proliferation, migration and invasion via targeting SOX4, which provided a novel therapeutic target for BC patients.